Did scarce global savings finance the US real estate bubble? The "Global Saving Glut" thesis from a stock flow consistent perspective - Fabian Lindner (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2015)
There is a consensus among the majority of economists that the credit supply is limited by current household saving. If governments or foreigners ran deficits, they would absorb this limited saving so that firms could not borrow any longer and had to reduce their investment. This is the "Loanable Funds" theory. Ben Bernanke's "Global Saving Glut" thesis is based on this view. According to Bernanke, the US depended on South East Asian and commodity exporting countries' scarce saving to finance the US real estate boom. Using simple accounting rules, the article shows however that credit is never limited by current saving. Often, the exact opposite is true: people can only save after others have taken on credit and paid incomes. This is also the case with the US and its trade partners and creditors: since non-Americans accept the US-Dollar as a means of payment - which only the US can produce - Americans give credit to themselves to finance their current account deficits. Each Dollar that non-Americans invest in the US has either been earned or borrowed in the US before. By their deficits, the US does not absorb scarce saving but allows other countries to increase their income and saving. – – Unter der Mehrheit der Ökonomen herrscht der Konsens, dass das Kreditangebot durch die laufende Haushaltsersparnis begrenzt sei. Wären Regierungen oder das Ausland im Defizit, würden sie diese begrenzte Ersparnis absorbieren, die dann nicht mehr als Kredite für Unternehmen zur Verfügung stünden. Diese müssten dann ihre Investitionen reduzieren. Dies ist die "Loanable Funds"-Theorie. Auch Ben Bernankes "Saving Glut"-Theorie basiert auf dieser Sicht. Nach Bernanke hingen die USA zur Finanzierung ihres Leistungsbilanzdefizits von den knappen Ersparnissen Südostasiens sowie rohstoffexportierender Länder ab. Unter Gebrauch einfacher Buchhaltungsregeln zeigt dieser Aufsatz allerdings, dass Kredite niemals durch laufende Ersparnis begrenzt sind. Oft ist das genaue Gegenteil wahr: Wirtschafter können nur sparen, wenn andere Wirtschafter einen Kredit aufgenommen und damit Einkommen gezahlt haben. Das ist auch der Fall für die USA und ihre Handelspartner und Gläubiger: Da Nicht-Amerikaner US-Dollar als Zahlungsmittel akzeptieren - die nur die USA selbst herstellen können - geben Amerikaner sich in letzter Instanz selbst Kredit, um ihre Leistungsbilanzdefizite zu finanzieren. Jeder Dollar, den ein Nicht-Amerikaner in den USA investiert, muss vorher in den USA geliehen oder verdient werden. Mit ihrem Defizit absorbieren die USA keine knappe Ersparnis, sondern erlauben erst dem Rest der Welt, überhaupt Ersparnis zu bilden.
urn:nbn:de:101:1-201602194998
Keywords: B2; B4; E2; E5; F3; 330; Investment; Finance; Saving; Current Account Imbalances; Credit Supply; Global Saving Glut; Loanable Funds Theory; Financial Crisis